2018
DOI: 10.1021/acschemneuro.8b00436
|View full text |Cite
|
Sign up to set email alerts
|

Conformational-Switch Based Strategy Triggered by [18] π Heteroannulenes toward Reduction of Alpha Synuclein Oligomer Toxicity

Abstract: A water-soluble meso-carboxy aryl substituted [18] heteroannulene (porphyrin) and its Zn-complex have been found to be viable in targeting α-Syn aggregation at all its key microevents, namely, primary nucleation, fibril elongation, and secondary nucleation, by converting the highly heterogeneous and cytotoxic aggresome into a homogeneous population of minimally toxic off-pathway oligomers, that remained unexplored until recently. With the EC 50 and dissociation constants in the low micromolar range, these hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 67 publications
2
7
0
Order By: Relevance
“…At this point in time, it was found that aSyn developed minor parallel b-sheet content which steadily increased with the passage of time (Table S3 †). In this context, our results are in agreement with previous ndings by Chakraborty et al 25 and Celej et al, 56 where it was reported that aSyn brillization is characterized by 'random coil / anti-parallel b-sheet / parallel b-sheet' secondary structural changes, however, differ from the results obtained by Ghosh et al, 57 where it was observed that aSyn, forms brils via an a-helix rich intermediate. On the other hand, in the presence of 0.75 mg ml À1 Triphala, aSyn did not show any structural change even up to 22 days of incubation and remained largely random coil ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…At this point in time, it was found that aSyn developed minor parallel b-sheet content which steadily increased with the passage of time (Table S3 †). In this context, our results are in agreement with previous ndings by Chakraborty et al 25 and Celej et al, 56 where it was reported that aSyn brillization is characterized by 'random coil / anti-parallel b-sheet / parallel b-sheet' secondary structural changes, however, differ from the results obtained by Ghosh et al, 57 where it was observed that aSyn, forms brils via an a-helix rich intermediate. On the other hand, in the presence of 0.75 mg ml À1 Triphala, aSyn did not show any structural change even up to 22 days of incubation and remained largely random coil ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…The TPPS synthesis was adapted from a previous report [25]. Briefly, the mixture of 5,10,15,20-tetraphenylporphyrin (0.2517 g) and 96% sulfuric acid (6 mL.…”
Section: Methodsmentioning
confidence: 99%
“…SHSY5Y cells were cultured in DMEM accompanied with 10% fetal bovine serum (FBS) and 1% antibiotic (PSN) under 5% CO2 in a humidified atmosphere at 37°C 21,40 . After 75-80% confluence, cells were harvested with 0.52 mM EDTA and 0.25% trypsin in phosphate buffered saline (PBS) and plated at the required density to allow them to re-equilibrate for a day before starting the experiment.…”
Section: Cell Culture and Cytotoxicity Assaysmentioning
confidence: 99%